Estrategias de recuperación de selvas en dos ejidos de Quintana Roo, México - Rebollar Domínguez, Silvia; Santos Jiménez, Victoria; Sánchez Aguilar, Rodolfo Luis (Instituto de Ecología, A.C., 2016)
With the purpose of attempting to solve the serious deforestation problem in Quintana Roo, the “Plan Piloto Forestal” was created in 1984 to be carried out in the state´s central and southern regions; from this project, civil organizations were born. That is the case of the Organización de Ejidos Productores de la Zona Maya, S.C. (OEPFZM). The ejidos Naranjal and Santa Maria belong to this Organization, whose forest production and conservation activities on the rain forest are considered in a forest management plan based on their particular ecological and physiological characteristics. Such plan was designed by a Forestry Technical Direction. In this paper, the management plan actions are described including the reforestation made, taken into account the forest inventory data, as well as the participation of campesinos in both ejidos taken as example of this organization. The permanent forest areas were established by the campesinos themselves gathered in an assembly, and the amount of cutting was decided based upon the forest inventories to define the existence of “precious” woods volumes along with the corresponding volumes of “common” or “less valuable” tropical woods. An important action is the promotion of the diversified use of the rain forest with wood species not commonly sold, which are well represented and whose potential use is evaluated with studies on their anatomy and technological characteristics. The technical advising, other interdisciplinary studies, the training of campesinos and the communal decision taking practice allow the adequate cutting and management of forest resources in a way compatible with its conservation.